Gait and Balance Impairments in Breast Cancer Survivors: A Systematic Review and Meta-analysis of Observational Studies - Hsieh, Katherine L. (Arch Rehabil Res Clin Transl, 2019)
OBJECTIVE: To systematically review and quantitatively synthesize gait and balance impairments in breast cancer survivors compared with age-matched controls or normative values for adults who never had breast cancer. DATA SOURCES: PubMed, Cumulative Index of Nursing and Allied Health, and Web of Science was searched using terms associated with breast cancer, mobility, and adult until November 2018. STUDY SELECTION: Studies were included if they were randomized control trials, cross-sectional, prospective, pre-post, or case-control by design, included adult breast cancer survivors, reported gait and/or balance metrics as primary or secondary outcomes, were peer-reviewed publications, and were written in English. The search yielded 2117 results with 29 studies meeting the inclusion criteria. DATA EXTRACTION: Two reviewers assessed study quality by the National Institutes of Health Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies to determine the strength of evidence for each study that met the inclusion criteria. Basic descriptors of each study, study protocol, and balance and gait measures were extracted. Meta-analysis was performed for the single leg stance, functional reach, center of pressure velocity, gait speed, and timed up and go. DATA SYNTHESIS: For quality assessment, 3 studies were rated good, 16 fair, and 10 poor. The meta-analysis indicated that there were no significant differences in single leg stance between breast cancer survivors and those who never had breast cancer (P=.33). Pooled values of the functional reach task (22.16cm; 95% CI, 8.98-35.33) and center of pressure velocity (1.2cm/s; 95% CI, 0.87-1.55) suggest balance impairment in breast cancer survivors when compared with normative values. Breast cancer survivors also performed worse than those who never had breast cancer in challenging balance conditions that reduced sensory information or altered base of support. Pooled gait speed at a usual speed (0.91m/s; 95% CI, 0.2-1.6), fast speed across a short distance (1.2m/s; 95% CI, 0.31-2.1), and fast gait speed across a long distance (1.65m/s; 95% CI, 1.64-1.66) suggest gait impairments when compared with normative values. CONCLUSIONS: Breast cancer survivors may demonstrate gait and balance impairments compared with normative values. Clinicians should consider assessing changes in balance and gait in breast cancer survivors to improve functional independence and prevent fall-related injuries.